Pemaknaan Generasi Z Terhadap Representasi Konten Hubungan Ideal Dalam Platform Tiktok - Melita Ayu Caesari; Devi Purnamasari (Mediakom : Jurnal Ilmu Komunikasi, 2026)
This study examines how generation z interprets the representation of "relationship goals" content on the TikTok platform. TikTok has become an influential space for digital visualization, shaping new social standards and romantic ideals among young users. Using Stuart Hall's Reception Analysis approach and Leon Festinger's Social Comparison Theory, this research explores the dynamic encoding-decoding process when gen z users interact with aesthetic romance content. In-depth interviews and digital participant observations were conducted over three months with six active female gen z TikTok users who are in relationships. The results indicate that visual exposure to idealized relationships prompts social comparison mechanisms, shifting real-world expectations and relationship satisfaction. The interpretation patterns reveal a dominant-hegemonic alignment where users internalize these aesthetic benchmarks as the normative blueprint for modern romance, while also highlighting the psychological pressures of conforming to digital perfection.